Decarbonization of Ukrainian Economy: Economic and Legal Issues - Zharova Liubov (EDP Sciences, 2021)
The research hypothesis is determined by its focus on forming practical proposals for creating a compelling economic and legal mechanism for the decarbonization of the economy. Based on an integrated approach to the regulation of relevant relations. This approach allows us to identify priority areas for the transformation of legal regulation in the context of decarbonization of the economy, which in turn will help lay the legal foundations for the transition to a carbon-free economy. The practical implementation of the study’s scientific results will contribute to implementing the tasks of the Renewed Nationally Defined Contribution of Ukraine to the Paris Agreement. It is planned to pay special attention to the legal aspects of modernization of the coal industry in the context of stimulating the reduction of greenhouse gas emissions. Additional attention was paid to the development of theoretical provisions and practical proposals for the harmonization of state policy in the field of bioenergy, its legal framework with the goals of decarbonization of the energy sector, and ensuring climate neutrality.